Streets of blood - Kilmer, Val, 1959-; Winkler, Charles; Lerner, Avi.; 50 Cent (Musician); Stone, Sharon; Hess, Eugene (Beverly Hills, CA : Anchor Bay Entertainment, 2009)
In New Orleans after 'Katrina', the partner of Detective Andy Devereaux is found dead, and he is teamed up with Stan Green. During the investigations, an undercover DEA agent is murdered by two dirty police officers. A psychologist, Nina Ferraro, has successive interviews with Andy, Stan and the two detectives. Meanwhile, the FBI also investigate the corruption in the police force leaded by Agent Brown.
Originally produced as a motion picture in 2008.
Title from disc surface.
Director of photography, Roy H. Wagner ; edited by Clayton Halsey ; music by Stephen Endelman.
Val Kilmer, Curtis "50 Cent" Jackson, Sharon Stone.
MPAA rating: R for strong violence, sexuality, drug content and pervasive language.
DVD; region 1; anamorphic widescreen.
Keywords: Police corruption -- Louisiana -- New Orleans -- Drama; Hurricane Katrina, 2005 -- Drama; New Orleans (La.) -- Drama; Police films; Crime films; Thrillers (Motion pictures); Feature films; Fiction films; Video recordings for the hearing impaired